2013
DOI: 10.4269/ajtmh.12-0642
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Extended-Spectrum Beta-Lactamases in a Major Teaching Hospital in Ghana: The Need for Regular Monitoring and Evaluation of Antibiotic Resistance

Abstract: Infections with bacteria producing extended-spectrum beta-lactamases (ESBLs) are increasing across Africa. This study reports on ESBL-producing Enterobacteriaceae as significant causes of infections and antibiotic resistance at Korle-Bu Teaching Hospital in Accra, Ghana. Of 300 isolates examined, 49.3% produced ESBLs. The prevalence of ESBLs was significantly high among isolates from neonates (28 of 43, 65.1%; relative risk = 1.62, 95% confidence interval = 1.33–2.13, P = 0.002) and adult patients > 65 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
62
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 16 publications
(21 reference statements)
42
62
6
Order By: Relevance
“…This observation is in agreement with previous studies in Ghana and at Korle-Bu teaching Hospital, that found high resistance to ampicillin, gentamicin and cefotaxime among Gram negative isolates [2325]. It is also the experience in KBTH that resistance to many routinely used antibiotics is high; and the prevalence is rising [25]. The pattern of resistance further mirrors findings from other developing countries were ampicillin and gentamicin have been found not to be very effective [4].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in agreement with previous studies in Ghana and at Korle-Bu teaching Hospital, that found high resistance to ampicillin, gentamicin and cefotaxime among Gram negative isolates [2325]. It is also the experience in KBTH that resistance to many routinely used antibiotics is high; and the prevalence is rising [25]. The pattern of resistance further mirrors findings from other developing countries were ampicillin and gentamicin have been found not to be very effective [4].…”
Section: Discussionsupporting
confidence: 93%
“…Cloxacillin/gentamicin had improved coverage over the national treatment guidelines, and remained the most active antibiotic combination despite a moderate coverage of <65.6 % for all bacterial isolates (with or without CoNS). This observation is in agreement with previous studies in Ghana and at Korle-Bu teaching Hospital, that found high resistance to ampicillin, gentamicin and cefotaxime among Gram negative isolates [2325]. It is also the experience in KBTH that resistance to many routinely used antibiotics is high; and the prevalence is rising [25].…”
Section: Discussionsupporting
confidence: 91%
“…The majority of ESBL producers were recovered from urine specimens (56.6%) and pus (22.7%). This is consistent with data reported in other studies (Obeng-Nkrumah et al, 2013;Severin et al, 2010). Our findings confirm the reports of Pitout et al (Pitout and Laupland 2008) showing higher frequencies of ESBL-producing Enterobacteriaceae among patients with severe infections including UTIs, suppurative infections, bacteremia, and intra-abdominal.…”
Section: Esbl-supporting
confidence: 94%
“…The overall pooled ESBL proportion estimate for East African hospitals (42 %) is close to estimates for Ghana (49 %), Cameroon (54 %), Gabon (45 %) and Morocco (43 %) [18, 3234]. This estimate is also close to data reported for China, where a nationwide survey that included 30 hospitals reported over 46 % resistance due to ESBL [35].…”
Section: Discussionsupporting
confidence: 76%